2010
DOI: 10.5468/kjog.2010.53.10.940
|View full text |Cite
|
Sign up to set email alerts
|

A case of primary restless leg syndrome aggravated by pregnancy

Abstract: Restless leg syndrome (RLS) is characterized by intense restlessness and unpleasant creeping sensations deep inside the lower legs, occurring during periods of rest, evening and night. These symptoms can be improved by movement. There are two different phenotypes of RLS. One early-onset form starts before 36 years old. It has mostly a familial history, severe symptoms, and highly genetically determined. And it is a highly dependent to iron level of the brain. The other delayed-onset form starts after 36 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…These results are consistent with those of previous studies that found that JJT was the most frequently used prescription [ 20 ]. JJT is a popular prescription mainly used for menstrual disorders and female infertility, and has been studied in several case reports [ 24 26 ] and experimental studies [ 27 , 28 ]. BCB is a prescription for ovulation and implantation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of previous studies that found that JJT was the most frequently used prescription [ 20 ]. JJT is a popular prescription mainly used for menstrual disorders and female infertility, and has been studied in several case reports [ 24 26 ] and experimental studies [ 27 , 28 ]. BCB is a prescription for ovulation and implantation.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating the effectiveness of an herbal-based obesity management program on an obese PCOS patient concluded that Changbudodam-tang (Cangfu Daotan-tang) is effective in treating oligomenorrhea associated with obesity in PCOS [20]. Additionally, herbal prescriptions such as Chokyung-san (Tiaojing-san), Changbudodamtang (Cangfu Daotan-tang), Onkyung-tang (Wenjingtang), Gyejibokryeong-hwan (Guizhi Fuling-wan), and Chokyungjongok-tang (Tiaojing Zhongyu-tang) were found to alleviate ovulatory dysfunction and apoptosis of granulosa cells, normalize the endometrium, and improve acne vulgaris, oligomenorrhea and excess androgen-related conditions associated with female ovarian dysfunction [21][22][23]. Several studies using animal PCOS models also tested the effectiveness of major herbal medicine prescriptions, such as Chokyung-san (Tiaojing-san), Gamiguibi-tang (Jiawei Guipi-tang), and Changbudodam-tang (Cangfu Daotan-tang) [23][24][25][26][27], and presented favorable results.…”
Section: Potential Mechanism and Implication For Researchmentioning
confidence: 99%